Global surgery: Improving health in low-income countries (Bangladesh Journal of Medical Science, 2021)
The aim of this report is to examine the definition of global surgery, discuss the problems and propose some suggestions. Global surgery aims to improve the surgical conditions to maintain a standard and equal surgical care, especially in low- and middle-income countries where burden of surgical diseases are increasing over the years. According to Lancet Commission on Global Surgery, 1.27 million more surgical healthcare workers will be required to provide minimal surgical workforce, by 2030. In resource-limited settings of the world-wide where medical education and post-graduation training programs are disrupted due to brain drain, instable conditions and economic reasons, sustaining a standard and accessible surgical care are possible by training surgeons.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.483-486